The role of National Public Security Plans in inducing public municipal security policies - Delgado, Leticia Fonseca Paiva (2022)
Brazilian municipalities have been increasing their spending in the public security field, including the creation of instances for the local management of urban violence, such as: municipal guards, secretariats and municipal public security councils (or similar instances). Given that, the main objective of this article is to identify how the National Public Security Plans have induced (or still induce) greater municipal involvement in this field. Having as its initial mark the Federal Constitution of 1988 and its final mark the law no 11675 of June 11, 2018, which instituted the Unified Public Security System (SUSP), this article hypothesizes that the greater participation of the municipality in public security is not only a result of adherence to the structuring values of Citizen Public Security concept, but also an attempt by these entities to adapt to the guidelines brought by successive national public security policies.